Community Resilience in the Context of Tourism Village Development - Pribudi, Anggarani; Supardal, Supardal (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community resilience plays a critical role in the sustainable development of Indonesian tourism villages. Through a semi-systematic literature review, this study examined the key factors that contribute to enhancing community resilience in Indonesian tourism villages. The analysis identified three major elements essential for building community resilience: adaptive capacity, empowerment and participation, and collaborative efforts with stakeholders. Key challenges include human resource limitations, inadequate infrastructure, cultural sustainability concerns, and uneven community participation. Strategies to address these challenges include implementing digital marketing approaches, developing integrated management systems, building community capacity, and fostering partnerships. The findings highlight the importance of a holistic, interdisciplinary approach that balances economic benefits with environmental and cultural preservation while ensuring active stakeholder involvement. By strengthening these elements of community resilience, tourism villages in Indonesia can create sustainable, equitable, and culturally vibrant tourism experiences.